Safeguarding PU air filter production: design innovations for risk management - Haziman, Zakaria; Faiz, Azizul; Fernando, Yudi; Diyana, Kamarudin (Politeknik Sultan Haji Ahmad Shah & Unit Penyelidikan dan Inovasi Politeknik, 2023)
As Malaysia's automotive industry drives economic growth, heightened competition has coincided with a rise in associated accidents (Ngu et al., 2020). This study focuses on the PU Air Filter Production Line at a top-tier Malaysian automotive parts manufacturer. It critically examines and optimizes a cutting machine's design, aiming to boost safety protocols substantially. Initiating with an indepth HIRARC analysis, the project evaluated existing occupational safety and health standards. A reengineered control measure followed, encompassing the launch of an upgraded cutting machine designed to diminish risks from high to medium, as indicated by HIRARC parameters. The new cutting machine's design followed a rigorous engineering process and was crafted using CATIA software. To affirm the blade's sturdiness, a static load analysis using CATIA confirmed its capacity to withstand the production's required force, with a comforting 2.5 safety factor. An economic evaluation validated the project's feasibility, reporting a 249.67% ROI and a payback period concluding at the end of quarter one. This study demonstrates the substantial advantages of this novel tool design, including risk reduction and a safer operational environment for staff.